No Difference in Perioperative Complications for Bilateral Total Knee Arthroplasty Staged at 1 Week Compared With Delayed Staging. Issue 20 (15th October 2022) - Johnson, Mitchell A.; Barchick, Stephen R.; Kerbel, Yehuda E.; DeAngelis, Ryan D.; Velasco, Brian; Nelson, Charles L.; Israelite, Craig L.
Abstract : Introduction: Controversy exists regarding the safety of simultaneous bilateral total knee arthroplasty (TKA) versus two TKA procedures staged months apart in patients with bilateral knee arthritis. Here, we investigated a third option: bilateral TKA staged 1 week apart. In this study, we examined the rate of complications in patients undergoing bilateral TKA staged at 1 week compared with longer time intervals. Methods: A retrospective review of 351 consecutive patients undergoing bilateral TKA at our institution was conducted. Patients underwent a 1-week staged bilateral procedure with planned interim transfer to a subacute rehabilitation facility (short-staged) or two separate unilateral TKA procedures within 1 year (long-staged). Binary logistic regression was used to compare outcomes while controlling for year of surgery, patient age, body mass index, and Charlson Comorbidity Index. Results: Two hundred four short-staged and 147 long-staged bilateral TKA patients were included. The average interval between procedures in long-staged patients was 200.9 ± 95.9 days. Patients undergoing short-staged TKA had a higher Charlson Comorbidity Index (3.0 ± 1.5 versus 2.6 ± 1.5, P = 0.017) with no difference in preoperative hemoglobin ( P = 0.285) or body mass index ( P = 0.486). Regression analysis demonstrated that short-staged patients had a higher likelihood of requiring a blood transfusion (odds ratio 4.015, P = 0.005) but were less likely to return to the emergency department within 90 days (odds ratio 0.247, P = 0.001). No difference was observed in short-term complications ( P = 0.100), 90-day readmissions ( P = 0.250), or 1-year complications ( P = 0.418) between the groups. Conclusion: Bilateral TKA staged at a 1-week interval is safe with a comparable complication rate with delayed staged TKA, but allows for a faster total recovery time. Level of evidence: Level III